2015
DOI: 10.1007/s00125-015-3636-2
|View full text |Cite|
|
Sign up to set email alerts
|

A systems view of type 2 diabetes-associated metabolic perturbations in saliva, blood and urine at different timescales of glycaemic control

Abstract: Aims/hypothesisMetabolomics has opened new avenues for studying metabolic alterations in type 2 diabetes. While many urine and blood metabolites have been associated individually with diabetes, a complete systems view analysis of metabolic dysregulations across multiple biofluids and over varying timescales of glycaemic control is still lacking.MethodsHere we report a broad metabolomics study in a clinical setting, covering 2,178 metabolite measures in saliva, blood plasma and urine from 188 individuals with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 59 publications
7
82
0
Order By: Relevance
“…(Green line of fit depicts the healthy control subjects and orange line of fit depicts the type 2 diabetes mellitus subjects) Table 4]. The present study is in unanimous agreement with studies done by Barnes et al, [19] Mook-Kanamori et al, [11] and Yousri et al [20] A study of this magnitude provides a comprehensive association of metabolic pathway with DM in two biofluids from the same patient. Taken together, our data suggest that 1, 5-AG in saliva constitutes a non-invasive marker for deregulated short-term glycemic control, reflecting glycemic status over the previous 48 h-2 weeks.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…(Green line of fit depicts the healthy control subjects and orange line of fit depicts the type 2 diabetes mellitus subjects) Table 4]. The present study is in unanimous agreement with studies done by Barnes et al, [19] Mook-Kanamori et al, [11] and Yousri et al [20] A study of this magnitude provides a comprehensive association of metabolic pathway with DM in two biofluids from the same patient. Taken together, our data suggest that 1, 5-AG in saliva constitutes a non-invasive marker for deregulated short-term glycemic control, reflecting glycemic status over the previous 48 h-2 weeks.…”
Section: Discussionsupporting
confidence: 91%
“…The mean salivary 1, 5-AG levels are slightly lower in males compared to that of females in G1 (2163.69%, 342.7%) and vice versa in G2 and are in agreement with studies done by Mook-Kanamori et al [11] This is attributed to the duration of DM and when duration was adjusted that the difference between male and female was not significant. On the contrary, studies done by Yousri et al [20] reported that female has lower mean salivary 1, 5-AG levels compared to males. [20] This difference could be due to the physical differences in the renal excretion between genders.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…72 Furthermore, a metabolic study on humans showed the association of 94 metabolites from different body fluids with T2DM. 73 However, an important limitation of the current metabolomics technology concerns the restricted number of metabolites that can be identified.…”
Section: Transgenerational Epigenetic Inheritance Of T2dmmentioning
confidence: 99%
“…1,5-anhydroglucitol, norvaline and l-aspartic acid, were found to be associated with macroalbuminuric diabetic kidney disease (11,12), while glutamine, glutamic acid and symmetric dimethylarginine (ADMA) were suggested as potentially-predictive biomarkers of diabetic complications (13)(14)(15). Several metabolites (e.g., α-hydroxybutyrate, βhydroxypyruvate and 1,5-anhydroglucitol (1,5-AG)), were associated with regulation of glycemic control (16,17). Many lipids were identified as predictive biomarkers of diabetes.…”
Section: Introductionmentioning
confidence: 99%